Combined metabolic stress and nitric oxide synthase inhibition induces tissue-specific remodeling across cardiovascular and hematopoietic compartments during obesity - Julia Drolet; Sergio D. Gomez Navarro; Ian M. Davis; Madison Babcock; Aric Lechner; Norifumi Urao (Frontiers in Cardiovascular Medicine, 2026)
Obesity-associated cardiometabolic disease is characterized by tissue-specific remodeling across cardiovascular, immune, and skeletal tissues. However, the integrated effects of combined metabolic stress and nitric oxide synthase (NOS) inhibition on these organ systems remain incompletely understood. We investigated whether long-term high-fat diet (HFD) feeding combined with NOS inhibition by L-NAME differentially remodels multiple organs during obesity progression. Male C57BL/6J mice were fed chow, HFD (60% kcal from fat), or HFD supplemented with constitutive NOS inhibition by L-NAME (0.5 g/L drinking water) for 15 weeks. HFD increased body weight, cardiac hypertrophy, myocardial fibrosis, and circulating myeloid-cell expansion compared with chow-fed controls. In contrast, L-NAME supplementation did not further increase body weight, cardiac hypertrophy, myocardial fibrosis, or collagen type I/type III ratio. Obesity-associated expansion of circulating neutrophils and inflammatory Ly6C hi monocytes was not observed in HFD + L-NAME mice, and instead, HFD + L-NAME selectively enhanced bone marrow remodeling, characterized by increased marrow adiposity and reduced trabecular bone volume. These findings demonstrate that combined HFD and NOS inhibition does not uniformly exacerbate obesity-induced pathology but instead elicits tissue-specific remodeling across organ systems. Under these experimental conditions, we highlight the bone marrow as a tissue prominently remodeled during combined metabolic stress and NOS inhibition, identifying the hematopoietic niche as a previously underappreciated target of cardiometabolic stress.